Exploring the Predictive and Theoretical Validity of the Network Interdependence Measure. Issue 5 (20th October 2019) - Stein, James B.; Davidson, Michael J.
ABSTRACT: This study used measures of social network interference and facilitation to add to the heuristic value of relational turbulence theory. This manuscript advances theory and the value of network interdependence measures by relating them to measures of partner interdependence, as well as measures of negative emotions. Longitudinal results revealed that time 1 network interference predicted time 2 partner interference. Moreover, time 1 partner facilitation predicted time 2 network facilitation. Competing mediated models revealed that time 2 partner interference mediates the relationship between time 1 network interference and time 2 negative emotions. Time 2 network interference partially mediated the relationship between time 1 partner interference and time 2 negative emotions. Results are discussed in terms of theoretical, conceptual, and statistical value.